Using speaking as a springboard to academic writing: a successful pedagogical experience - Arruda, Climene Fernandes Brito; Murphy, Lukas John (Letras, 2022)
English for Academic Purposes (EAP) is at the forefront of "both theory development and innovative practice in teaching English as a second/other language" Hyland (2006, p.1), as it has become the predominant language in science and research. However, many EAP courses still lack a theoretical rationale, and teachers rely on textbooks or teaching experiences to develop their own methodology and material. Based on Newton (2018), Kroll & Vann (1981) and Weissberg (2006), this contribution reports on a successful pedagogical experience that connected the use of speaking to foster the development of academic writing of EAP students in a Brazilian university.